Flood-driven jet flow and sedimentary regime in a river-dominated estuary - Liu, Jing; Lin, Yitong; He, Zixiao; Liu, Feng; Jia, Liangwen; Wei, Wen (Frontiers in Marine Science, 2023)
Sediment dynamics under floods are critical for estuarine morphological evolution. A two-dimensional coupled hydrodynamic/sediment transport numerical modeling was adapted to investigate the flood-driven jet structure and the resultant sedimentary regime in a river-dominated estuary, Modaomen Estuary, Pearl River Delta, China. The results show that the flow velocity of flood jet exhibits a Gaussian distribution in the transverse direction and shows a linear decreasing trend in the longitudinal direction. Moreover, a distinct zonation, including a zone of flow establishment (ZOFE) and a zone of established flow (ZOEF), was detected. The ZOFE was the core area of high turbidity and strong erosion and provided sufficient sediments to the ZOEF, where sediment diffused and settled. Due to the settling lag, the sediment diffusion and deposition areas were larger than those of the jet. Estuarine geomorphology regulates the shape of flood jet, which shows an asymmetry configuration with the main body located at the west side of the bifurcated estuary. Tidal dynamics play a crucial role in altering the range of jet diffusion, especially in the longitudinal direction. Increased flood intensity has little effect on the jet structure and erosion/deposition pattern, but significantly increases the magnitude of seaward current velocities and bed level changes, as well as the transverse diffusion range of jet and sedimentation.